Cost and Management Accounting : An Introduction - Drury, Colin (Andover : South-Western Cengage Learning, 2011)
This is a text for introductory courses on cost and management accounting. It provides coverage of the elementary principles and techniques of costing and management accounting, and concentrates on the typical syllabus of a first year BA course.
Previous ed.: London: Thomson, 2006.
Includes bibliographical references and index.
Keywords: Cost accounting; Managerial accounting; Finance and Accounting